Animals are not cognitively stuck in time. (12th December 2019) - Viera, Gerardo; Margolis, Eric
Abstract: We argue that animals are not cognitively stuck in time. Evidence pertaining to multisensory temporal order perception strongly suggests that animals can represent at least some temporal relations of perceived events.